PENGARUHÃÂ KELENGKAPANÃÂ PERALATANÃÂ PRAKTIKÃÂ DANÃÂ PENERAPANÃÂ KESELAMATANÃÂ ÃÂ DANÃÂ KESEHATANÃÂ KERJAÃÂ TERHADAPÃÂ HASILÃÂ BELAJARÃÂ KOMPETENSIÃÂ PERBAIKANÃÂ KOPLINGÃÂ ÃÂ ÃÂ - Ami, Ridwan; Masugino, -; PramonoÃƒÂ‚Ã‚Â , - (Jurnal Pendidikan Teknik Mesin, 2008)
PenelitianÃÂ iniÃÂ bertujuanÃÂ untukÃÂ mengetahuiÃÂ seberapaÃÂ besarÃÂ pengaruhÃÂ kelengkapanÃÂ peralatanÃÂ praktikÃÂ danÃÂ penerapanÃÂ  keselamatanÃÂ  danÃÂ  kesehatanÃÂ  kerjaÃÂ  terhadapÃÂ  hasilÃÂ  belajarÃÂ  kompetensiÃÂ  perbaikanÃÂ  koplingÃÂ  diÃÂ  SMKÃÂ  NÃÂ  1ÃÂ AdiwernaÃÂ KabupatenÃÂ TegalÃÂ menurutÃÂ persepsiÃÂ siswa.ÃÂ SampelÃÂ dalamÃÂ penelitianÃÂ  iniÃÂ sebanyakÃÂ 70ÃÂ siswaÃÂ yangÃÂ diambilÃÂ menggunakanÃÂ  teknikÃÂ  totalÃÂ  sampling.ÃÂ  MetodeÃÂ  pengambilanÃÂ  dataÃÂ  menggunakanÃÂ  angketÃÂ  yangÃÂ  telahÃÂ  diujiÃÂ  validitasÃÂ reliabilitasnya.ÃÂ MetodeÃÂ  analisisÃÂ  dataÃÂ  danÃÂ  hipotesisÃÂ menggunakanÃÂ  analisisÃÂ  regresiÃÂ  duaÃÂ  prediktor.ÃÂ HasilÃÂ  penelitianÃÂ menunjukkanÃÂ  bahwaÃÂ  kelengkapanÃÂ  peralatanÃÂ  praktikÃÂ  danÃÂ  penerapanÃÂ  keselamatanÃÂ  danÃÂ  kesehatanÃÂ  kerjaÃÂ  secaraÃÂ bersamaÃ¢â¬ÂsamaÃÂ memberikanÃÂ pengaruhÃÂ terhadapÃÂ hasilÃÂ belajarÃÂ kompetensiÃÂ perbaikanÃÂ koplingÃÂ diÃÂ SMKNÃÂ 1ÃÂ AdiwernaÃÂ KabupatenÃÂ  Tegal.ÃÂ  DisarankanÃÂ  kepadaÃÂ  sekolahÃÂ  untukÃÂ meningkatkanÃÂ  kelengkapanÃÂ  peralatanÃÂ  praktiknyaÃÂ  danÃÂ  guruÃÂ untukÃÂ  selaluÃÂ mengawasiÃÂ  siswaÃÂ padaÃÂ  saatÃÂ pembelajaranÃÂ praktikÃÂ berlangsungÃÂ agarÃÂ  siswaÃÂ  terkontrolÃÂ  jikaÃÂ adaÃÂ  siswaÃÂ yangÃÂ tidakÃÂ menerapkanÃÂ keselamatanÃÂ danÃÂ kesehatanÃÂ kerja. ÃÂ  KataÃÂ kunci:ÃÂ KelengkapanÃÂ peralatanÃÂ praktik,ÃÂ keselamatanÃÂ danÃÂ kesehatanÃÂ kerja,ÃÂ hasilÃÂ belajarÃÂ ÃÂ TheÃÂ aimÃÂ ofÃÂ theÃÂ researchÃÂ isÃÂ toÃÂ discoverÃÂ howÃÂ muchÃÂ theÃÂ effectÃÂ ofÃÂ practiceÃÂ toolÃÂ completeness,ÃÂ workingÃÂ healthÃÂ andÃÂ safetyÃÂ applicationÃÂ towardÃÂ competenceÃÂ studyÃÂ resultÃÂ ofÃÂ clutchÃÂ repairÃÂ isÃÂ atÃÂ SMKÃÂ NÃÂ 1ÃÂ AdiwernaÃÂ inÃÂ TegalÃÂ RegencyÃÂ acÃ¢â¬ÂcordingÃÂ  toÃÂ  studentsÃ¢â¬â¢ÃÂ perceptions.ÃÂ TheÃÂ  sampleÃÂ ofÃÂ  theÃÂ  researchÃÂ wasÃÂ aboutÃÂ 70ÃÂ  studentsÃÂ  chosenÃÂ usingÃÂ  totalÃÂ  samplingÃÂ technique.ÃÂ DataÃÂ wasÃÂ gotÃÂ usingÃÂ questionnaireÃÂ havingÃÂ beenÃÂ testedÃÂ inÃÂ validityÃÂ ofÃÂ itsÃÂ reliability.ÃÂ Meanwhile,ÃÂ theÃÂ dataÃÂ andÃÂ hypothesisÃÂ wereÃÂ analyzedÃÂ usingÃÂ twoÃ¢â¬ÂpredictorÃÂ regressionÃÂ analysis.ÃÂ TheÃÂ resultÃÂ ofÃÂ theÃÂ researchÃÂ indicatesÃÂ thatÃÂ practiceÃÂ toolÃÂ completeness,ÃÂ workingÃÂ healthÃÂ andÃÂ safetyÃÂ applicationÃÂ simultaneouslyÃÂ  contributeÃÂ  impactÃÂ  towardÃÂ  competenceÃÂ studyÃÂ resultÃÂ ofÃÂ clutchÃÂ repairÃÂ atÃÂ SMKÃÂ NÃÂ 1ÃÂ AdiwernaÃÂ inÃÂ TegalÃÂ Regency.ÃÂ ItÃÂ isÃÂ suggestedÃÂ toÃÂ hadmasterÃÂ toÃÂ affordÃÂ theÃÂ practiceÃÂ toolÃÂ completenessÃÂ andÃÂ toÃÂ teachersÃÂ toÃÂ keepÃÂ theirÃÂ eyesÃÂ onÃÂ studentsÃÂ whenÃÂ aÃÂ learningÃÂ practiceÃÂ lastsÃÂ soÃÂ thatÃÂ theÃÂ studentsÃÂ areÃÂ inÃÂ controlÃÂ andÃÂ alwaysÃÂ concernÃÂ withÃÂ workingÃÂ healthÃÂ andÃÂ safety. ÃÂ  Keywords:ÃÂ practiceÃÂ toolÃÂ completeness,ÃÂ workingÃÂ healthÃÂ andÃÂ safety,ÃÂ studyÃÂ result